2013
DOI: 10.1104/pp.113.222380
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Network-Based Approach Dissects Late Maturation Processes Related to the Acquisition of Desiccation Tolerance and Longevity of Medicago truncatula Seeds

Abstract: In seeds, desiccation tolerance (DT) and the ability to survive the dry state for prolonged periods of time (longevity) are two essential traits for seed quality that are consecutively acquired during maturation. Using transcriptomic and metabolomic profiling together with a conditional-dependent network of global transcription interactions, we dissected the maturation events from the end of seed filling to final maturation drying during the last 3 weeks of seed development in Medicago truncatula. The network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
214
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(221 citation statements)
references
References 75 publications
(120 reference statements)
7
214
0
Order By: Relevance
“…Our comparative transcriptomic analysis of desiccation-tolerant and -intolerant mutants identified biological processes important for DT acquisition in seeds and coincides with findings from previous reports (3,37). However, there is no information available on TFs that regulate the genetic networks involved in the acquisition of seed DT.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our comparative transcriptomic analysis of desiccation-tolerant and -intolerant mutants identified biological processes important for DT acquisition in seeds and coincides with findings from previous reports (3,37). However, there is no information available on TFs that regulate the genetic networks involved in the acquisition of seed DT.…”
Section: Discussionsupporting
confidence: 71%
“…In angiosperms, DT is acquired at the seed maturation stage, which involves a complex regulatory network (3,4) that activates a large subset of genes involved in a number of mechanisms that influence seed survival in the dry state. The set of genes required for seed DT includes genes encoding protective proteins such as late embryogenesis abundant (LEA) (5,6) and heat shock proteins (HSPs) (7), enzymes involved in scavenging reactive oxygen species (8) and the biosynthesis of protective compounds such as oligosaccharides (3,9), and antioxidants such as tocopherols and flavonoids (10,11).…”
mentioning
confidence: 99%
“…These transcriptional regulators were projected onto MatNet ( Figure 2C, red symbols). Using data from the Medicago Gene Expression Atlas MtGEA (He et al, 2009) and our own transcriptomic data sets (Verdier et al, 2013), we also identified probes preferentially expressed in seeds in comparison to other tissues. Out of the 2912 nodes present in MatNet, 198 had transcription levels >100-fold higher in seed versus non-seed tissues (blue symbols).…”
Section: Generation and Characterization Of Matnet: A Robust Coexpresmentioning
confidence: 99%
“…This uncoupling suggests that the acquisition of these traits is controlled in part by independent regulatory pathways. To test this hypothesis and further elucidate the extent to which genes in the DT and longevity modules are under regulation of ABI3, we analyzed the transcriptomes of the desiccation-sensitive seeds of M. truncatula abi3 mutants at 32 and 40 DAP (Delahaie et al, 2013;Verdier et al, 2013) (Supplemental Data Set 5). These time points coincide with an increase in the transcript levels of the longevity-correlated genes in wild-type seeds.…”
Section: Implication Of Medicago Abi3 In the Regulation Of The Desiccmentioning
confidence: 99%
See 1 more Smart Citation